Resposta morfo-sedimentar do estuário do rio Potengi aos impactos de dragagem - Santos, Allyson Benedito dos (2018)
The potengi estuary has undergone anthropic influences in the last decades, where these processes affected sediment distribution and bedforms. Changes in sedimentation patterns may result in habitat destruction, disturbances in physicochemical processes, changes in suspended sediment concentration, water eutrophication, and instability of estuarine sedimentary dynamics. This work aims to understand how estuarine sediments spread over decades and which factors control sedimentary dynamics in the Potengi estuary. To understand these changes, sedimentological and bathymetric data of the estuary were collected between 2003 and 2015 covering significant events such as: flooding, dredging and sewage treatment station. The recent sedimentological data show the existence of 10 faciological classes, with predominant siliciclastic facies along the main channel and the carbonate facies in the tidal channels, differently of the distribution sediments in 2003 that showed siliciclastic facies for the entire estuary. The main differences are granulometry reduction of the principal channel, representing a change from medium sand to fine sand, increase particle size in tidal channels, increase organic matter content throughout the estuary at levels greater than 3.0%, reduction the content calcium carbonate at the mouth of the Baldo channel and an increase of CaCO3 in the tidal channels. The bathymetric variation in the estuary between 2004 and 2014 is mainly due to the dredging carried out in 2010, with results the deepening of the channel with differences from up to 3m and increasing slope at the edges of the channel (7.5º - 22º). Changes in channel morphology after dredging show the reworking sediments in situ and adjustments in the river profile in relation to degraded areas. The estuary circulation is strongly controlled by tidal cycles affecting the bottom forms distribution and recent surface sediments. The comparison between data indicates a major marine influence in the carbonate sediments introduction among the estuary and the weak competence to export fluvial sediments and post-dredging in the short term.